Exploring the impacts of social media On EFL communication: Lecturers and students’ perspectives - Larasati, Ade Putri; Eryansyah (Edukasi, 2024)
This study was a descriptive qualitative study investigating the perceptions of EFL lecturers and students regarding the use of social media in EFL teaching and learning. It involved five lecturers and 67 EFL students of a state-owned university in South Sumatra as its research respondents. Two Likert-scale surveys were used to collect data and the data were analyzed using google form. Research findings showed that social media use in EFL teaching and learning was perceived favourably by both lecturers and students. They agreed that using social media to teach and learn English could help students become more proficient communicators, both in written and spoken forms. Their opinions regarding the usage of social media in EFL instruction may have been influenced by a number of factors, including the digital literacy of the lecturers and their background as educators who saw social media as an integral part of their pedagogy Students' familiarity with social media platforms may have also played a role in shaping their perceptions. They typically have good thoughts on social media use in EFL classes since they used them regularly in their daily lives and are aware of their benefits.